La perspectiva de la auto escucha de Reggio Emilia en el desarrollo de la creatividad en niños de educación inicial - Martinez Bustillos, Marylin Alexandra (2022)
In the following investigation, the purpose is to design a learning experience through the perspective of Self-Listening where Reggio Emilia's pedagogy emphasizes the development of children's creativity, helps to have a better performance in education and in the learning. Being an important pedagogical approach within Initial Education where the following research is based on the development of the following areas that are: cognitive, socio-affective and language. The direct beneficiaries in the use of this pedagogy are the children of the first year of Basic Parallel "A" of the School of Basic Education "United Nations", the parents and the teachers since this approach is developed through the children's creativity where a better development in learning is obtained and allows a better understanding between the student and teacher through listening where this Reggio Emilia pedagogy is based on experimentation and observation, where through of creativity can generate better learning capacities. Therefore, it provides us with multiple benefits such as the development of communication between the student and the teacher, it obtains the attention of the children, the children share social interactions with their peers, it helps in the development of children's hearing and vision since they are important organs, listening is important in education, therefore, it allows children to communicate not only through words but also through gestures, movements, art and through creativity.